Pengaruh Pendampingan Mobilisasi Dini Terhadap Nyeri Pada Pasien Sectio Caesarea Di RSUD Kabupaten Bekasi - Farlikhatun, Lili; Supardi, Retno (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To identify problem that arises after Sectio Caesare (SC) is pain due to the incision caused by tearing of the abdominal wall and uterine wall tissue. Postpartum mothers performed caesarean sections at the Bekasi Regency Hospital December 2023 – January 2024, namely 52 deliveries. One effort that can be made to relieve post-SC patient pain is early mobilization. To determine the effect of early mobilization assistance on pain intensity in post caesarean section patients at the Bekasi District Hospital Methods: This artikel The form of research design chosen was post-test only control group design. The population in this study was all postpartum mothers who had undergone SC surgery, totaling 52 mothers with a total of 27 control samples and case samples each. Data collection was carried out using a numerical rating scale (NRS) pain scale questionnaire. Hypothesis testing was carried out using the Mann-Whitney U test at a significance level of 0.05. Results: the majority of post-SC surgery mothers in the group without early mobilization assistance had a moderate pain scale, namely 25 people (93%); (2) all mothers (100%) after CS surgery in the group with early mobilization assistance had a mild pain scale; (3) there is an effect of early mobilization assistance on reducing pain intensity in post caesarean section patients, with p-value (0.000) < 0.05. Conclusion: there is an effect of early mobilization assistance on reducing pain intensity in post-cesarean section patients at the Bekasi District Hospital